Grace and Reconciliation as Gift. Issue 3 (15th September 2015) - Lodberg, Peter
Abstract: Through examples of grace and gift of reconciliation the meaning of grace is interpreted in relation to social and political transformation. Grace is understood as the unexpected kairotic moment of change, where the future opens up for new possibilities of reconciliation in situations of conflict. It is a moment you cannot plan for, but hope for to happen. Trusting in the possibility of a gracious moment can influence your work in the present. Hoping and waiting for the gracious moment of reconciliation is linked to a praxis of active nonviolence as seen in the work of Martin Luther King, Jr.